A Comprehensive Exploration of the Fatty Acids Profile, Cholesterol, and Tocopherols Levels in Liver from Laying Hens Fed Diets Containing Nonindustrial Hemp Seed - Youssef Rbah; Yassine Taaifi; Aymane Allay; Kamal Belhaj; Reda Melhaoui; Nadia Houmy; Abdessamad Ben Moumen; Embarek Azeroual; Mohamed Addi; Farid Mansouri; Hana Serghini-Caid; Ahmed Elamrani (Scientifica)
This study investigates the impact of dietary nonindustrial Moroccan hemp seed (HS) on the fatty acid profile, cholesterol, and tocopherol levels, in the liver of 120 Lohmann brown laying hens aged 22 weeks during 12 weeks of treatment. The hens are randomly allocated into four treatment groups, each subdivided into six replicates with five birds in each replicate. The dietary treatments consist of 0% HS (control), 10% HS, 20% HS, and 30% HS. Results indicate a substantial increase p<0.01 in polyunsaturated fatty acids, including omega 3 (n-3) and omega 6 (n-6) types, with the inclusion of HS in the diet. The n-6/n-3 ratio is significantly reduced p<0.01, and there is a significant reduction p<0.01 in saturated fatty acids only for the 30% HS treatment, indicating a more favorable fatty acid composition. Cholesterol levels remain largely unaffected by HS inclusion, except for the 10% HS group, which shows a significant decrease p<0.05. Moreover, hepatic tocopherol levels are significantly elevated p<0.01 in subjects receiving the HS diet, with the 30% HS group exhibiting the highest tocopherol content. In summary, incorporating HS into the diet up to 30% appears to offer promising benefits for hepatic lipid composition, particularly in terms of n-3 polyunsaturated fatty acids, the n-6/n-3 ratio, and tocopherol levels, while having minimal impact on cholesterol levels.